Alat Ukur Power Menendang Futsal Berbasis Mikrokontroler - Saputra, Ahmad Fauzi; Fitranto, Nur; Wardoyo, Hendro (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
The development of a kicking power measurement tool in futsal is crucial, considering the effectiveness of measurements in sports plays a significant role in achieving peak performance. This research aims to develop a futsal kicking power measurement tool based on microcontroller technology. The research method used is Research and Development with the ADDIE model. The five steps involved in developing this model include analysis, design, development, implementation, and evaluation. The research sample consisted of 15 U-15 futsal athletes from Rusun Rawa Bebek. The research findings show that the athletes' perception of the developed tool indicates that this kicking power measurement tool is